Analisis Isnad Cum Matn: Mengukur Kritik Hadis Muslim Dan Barat - Maizuddin M. Nur (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Islamic scholars have built the method of hadith criticism since the early times to determine the validity of a hadith. Similarly, the West has for long developed its own methods in contrast to hadith criticism by the Muslim scholars. Both methods built by the Muslims and the West have been widely accepted by the respective societies and have been used for academic interests. However, both methods are not free of criticism from the scholars. Some Muslim scholars have doubted the efficacy of the Muslim's criticism method of hadith. Similarly, in the West, some scholars also doubt the efficacy of hadith criticism by the Western methods. One of the criticisms came from Kamaruddin Amin, who criticized both the Muslim and Western methods. Kamaruddin Amin criticized by presenting a relatively new method. He attempted to apply the isnad cum matn method in his work Reassess the Accuracy of Hadith Criticism Methodology. He claimed that the analysis of the isnad cum matn had reached better results compared to other dating methods. However, there should be both appreciation and criticism of this method. This is the main concern of this article.